(untitled) (Bodhi Path, 2019)
Religion has been an inalienable part of human life transcending all time and space on this planet. History provides that the life of average citizen has been widely influenced by the impact of the practising religions of the land, be it Hinduism. Philosophy and religion, thus; from the very beginning of the mankind have shaped the life of the individual right from his birth till his death. The duties of human beings towards each other, including those of the king towards his subjects had been based on certain laws and canons evolved from time to time by the enlightened saints, philosophers and exponents of religion and culture. However, the nature and form of impact of the religion had varied from region to region, from state to state and from races to races. Evidences suggest that of all the philosophies and religions, Buddhism has possessed the imprint of such expressions to mould the life of the people throughout this large Indian subcontinent. And among the ancient Indian Kings who, in the spirit of a true follower of a religion or a dharma, had undertaken from time to time upon themselves the duty of organising activities of public welfare through state sponsored activities.